IbM Pemanfaatan Enceng Gondok Dan Jerami Sebagai Pakan Ternak Dan Pupuk Alternatif Di Desa Ngargorejo - Suryono Suryono (PRIMA: Journal of Community Empowering and Services, 2017)
Science and technology for society program (IbM) on Ngargorejo Village. The usage of  Water Hyacinth (Euchornia crassipes) and Straw as an Cattle Feed and Fertilizer Alternative in cooperation with two partners , namely : Mina Sejahtera Breeders Group and Ngudi Makmur Farmers Group Association subdistrict Ngargorejo Ngemplak Boyolali with the distance of about 20 km from UNS . Problems experienced by Mina Sejahtera Breeders Group can be identified as follows : the presence of water hyacinth disrupt fish farms as waters cover , water hyacinth removed only inside of reservoir and allowed to sit there . Problems experienced Gapoktan Ngudi Makmur is the availability of fertilizer is still highly dependent on chemical fertilizers manufactured, so greatly disrupt the smooth process of agricultural production and the price of chemical fertilizers manufactured, so unstable / erratic even tend to be expensive , which is ultimately detrimental to the farmers . The solutions offered to solve the problems that arise is to identify problems than continued training and practice composting of water hyacinth and straw as fertilizer and cattle feed . Outcomes that would result from the IbM action plan that will include a scientific article published by the journal in the University of Sebelas March and models / tools appropriate technology ( TTG ) in the form of trash thrasher, that partners used to make compost . As a result of this activities, training making cattle feed and fertilizer from water hyacinth and straw have been carried out. The delivery of aid water hyacinth and straw thrasher , and continued to the practice of making fertilizer and cattle feed from water hyacinth and straw.